Pancasila as a National Insight in the Modern Era - Yola Valencia; Shelvy Wahyuni; Raihanul Zaqi Pratama (Penerbit Hellow Pustaka, 2026)
As the ideology and foundation of the Indonesian state, Pancasila plays a crucial role in maintaining national unity. In this modern era, the challenges faced by the Indonesian nation are increasingly complex, particularly with globalization, technological development, and rapid socio-cultural change. Therefore, strengthening national insight based on Pancasila is becoming increasingly relevant. This study analyzes how Pancasila can function as a national insight in the modern era, as well as how to instill Pancasila values ​​among the younger generation. This study also aims to explore the challenges facing Pancasila in the context of the modern era and rapid social change. In the face of globalization and technological development, Pancasila is expected to function as a foundation of values ​​that unite Indonesian society. The results of the study indicate that strengthening Pancasila values ​​can create national solidarity and a strong national identity.